Measuring pediatric hematology–oncology fellows' skills in humanism and professionalism: A novel assessment instrument. Issue 5 (3rd November 2016) - Kesselheim, Jennifer C.; Agrawal, Anurag K.; Bhatia, Nita; Cronin, Angel; Jubran, Rima; Kent, Paul; Kersun, Leslie; Rao, Amulya Nageswara; Rose, Melissa; Savelli, Stephanie; Sharma, Mukta; Shereck, Evan; et al.
Abstract: Background: Educators in pediatric hematology–oncology lack rigorously developed instruments to assess fellows' skills in humanism and professionalism. Procedure: We developed a novel 15‐item self‐assessment instrument to address this gap in fellowship training. Fellows (N = 122) were asked to assess their skills in five domains: balancing competing demands of fellowship, caring for the dying patient, confronting depression and burnout, responding to challenging relationships with patients, and practicing humanistic medicine. An expert focus group predefined threshold scores on the instrument that could be used as a cutoff to identify fellows who need support. Reliability and feasibility were assessed and concurrent validity was measured using three established instruments: Maslach Burnout Inventory (MBI), Flourishing Scale (FS), and Jefferson Scale of Physician Empathy (JSPE). Results: For 90 participating fellows (74%), the self‐assessment proved feasible to administer and had high internal consistency reliability (Cronbach's α = 0.81). It was moderately correlated with the FS and MBI (Pearson's r = 0.41 and 0.4, respectively) and weakly correlated with the JSPE (Pearson's r = 0.15). Twenty‐eight fellows (31%) were identified as needing support. The self‐assessment had a sensitivity of 50% (95% confidence interval [CI]: 31–69) and a specificity of 77% (95% CI: 65–87) for identifying fellows who scored poorly on at least one of the three established scales. Conclusions: We developed a novel assessment instrument for use in pediatric fellowship training. The new scale proved feasible and demonstrated internal consistency reliability. Its moderate correlation with other established instruments shows that the novel assessment instrument provides unique, nonredundant information as compared to existing scales.